Imaging the rupture of the Mw 6.3 April 6, 2009 L'Aquila, Italy earthquake using back-projection of teleseismic P-waves - D'Amico, Sebastiano; Koper, Keith D.; Herrmann, Robert B.; Akinci, Aybige; Malagnini, Luca (Geophysical research letters, 2010)
We present rupture details of the Mw 6.3 April 6, 2009 L'Aquila earthquake derived by back‐projecting teleseismic P waves. This technique has previously been applied to large magnitude earthquakes, but this is the first application to a moderate size event. We processed vertical‐component seismograms for 60 broadband stations obtained from the Incorporated Research Institutions for Seismology (IRIS) data center. The traces were aligned and normalized using a multi‐channel cross‐correlation algorithm and 4th root stacking was used to image the rupture. We found that the L'Aquila earthquake ruptured towards the south and that a second discrete pulse of energy occurred 20–25 km east of the epicenter about 17–18 s after the nominal origin time. The spatial extent of the rupture image correlates well with a post‐seismic survey of damage in the region. Because the technique is potentially very fast (images can be produced within 20–30 minutes of the origin time), it may be useful to governmental agencies tasked with emergency response and rescue.